1986
DOI: 10.1007/bf02375001
|View full text |Cite
|
Sign up to set email alerts
|

Potassium requirements for growth and its related processes determined by plant analysis in wheat

Abstract: Summary Potassium requirements for growth --dry matter (DM) and leaf area (LA) and related processes --relative leaf growth rate (RLGR), relative growth rate (RGR), net assimilation rate (NAR) and crop growth rate (CGR) were determined by plant analysis during the entogeny of wheat. Wheat (Triticum aestivum cv. HD 2329) plants were supplied with different amounts of K from deficient to adequate through nutrient solution. Samples were taken at specific stages for K determinations. The DM and LA were recorded at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Some studies (Rao 1986;Nadia 2006) with crops have shown a dramatic increase in growth with increasing K addition, which has also been exhibited in these two cultivars in this study. However, different growth stages had different responses to K for both cultivars (Table 1).…”
Section: Effects Of Potassium On the Growth And Developmentsupporting
confidence: 63%
“…Some studies (Rao 1986;Nadia 2006) with crops have shown a dramatic increase in growth with increasing K addition, which has also been exhibited in these two cultivars in this study. However, different growth stages had different responses to K for both cultivars (Table 1).…”
Section: Effects Of Potassium On the Growth And Developmentsupporting
confidence: 63%
“…Leaf K + concentrations (Table 4) were within the sufficiency ranges presented by Rama Rao (1986). The small differences in K + concentration observed between nitrate-or ammonium-fed plants may be an indication of the low interference of the later ion in K + uptake when grown in sand.…”
Section: Potassium and Sodium Concentrationmentioning
confidence: 55%
“…A reduction in leaf growth has been commonly reported for moderately K-deficient plants of wheat (Rama 1986), soybean (Itoh et al 1987) and cotton (Xi and Lihua 1989;Pettigrew and Meredith 1997;Reddy et al 2000;Zhao et al 2001). The relative decrease in leaf area has been mainly associated with a reduction in the rate of leaf elongation (JordanMeille and Pellerin 2004).…”
Section: Introductionmentioning
confidence: 92%